Sustainability issues in the water supply sector of urban India: implications for developing countries. (24th July 2012) - Kulshrestha, Mukul; Vishwakarma, Amit; Phadnis, Sanjay Sitaram; Thakur, Tripta
Rapid urbanisation, growing cities, high population growths, public ownerships of utilities, misgovernance and malpractices, poverty, subsidies, lack of adequate finances, and inefficient operations etc. are some of the common problems characterising most developing economies. In this sense, the Indian urban water supply sector represents several issues that are common to the water supply utilities across developing countries. This paper elaborates the sustainability issues faced by the Indian water supply sector. It reviews the Indian urban scenario, and explores the role of the government in providing the water supplies to these urban areas. It also details the various sustainability issues in the water supply sector, and finally suggests some of the reform measures that are specific to the Indian conditions, but can be generalised to hold valid for most developing countries.